Building Apartment Developer Satisfaction with Brand Image, Value Co-Creation and Supply Chain Agility along with its Impact on Developer Loyalty Towards Apartment Contractors - Setijanto, Augustinus; Hardjomuljadi, Sarwono; Sulistio, Hendrik (LPPM of NAROTAMA UNIVERSITY, 2024)
Objective: Apartment sector is one of the important real estate sectors of a country. The aim of this research is to analyse the influence of brand image, value co-creation, and supply chain agility on customer satisfaction and its impact on developer loyalty to apartment contractors. The novelty of this research lies in analyzing the influence of brand image, value co-creation, and supply chain agility on customer satisfaction simultaneously in the context of the apartment construction industry. Design/ methodology/ approach: This research uses a quantitative approach with structured equation modeling using smartPLS. The population of this research is apartment developers in Indonesia. Findings: The results of this research show that brand image, value co-creation, and supply chain agility have a positive and significant influence on customer satisfaction. This research has theoretical implications for expectancy disconfirmation theory and service dominance logic. The managerial implications of this research are on apartment contractors' strategies for gaining developer satisfaction and loyalty. Paper type: Research paper